The Metabolic Syndrome in Hispanics – The Role of Insulin Resistance and Inflammation - Altieri, Pablo I.; Marcial, José M.; Escobales, Nelson; Crespo, María; Banchs, Héctor L. (IntechOpen, 2012)
None